2017
DOI: 10.1200/jco.2017.35.15_suppl.e14065
|View full text |Cite
|
Sign up to set email alerts
|

Results of bevacizumab biosimilar compared with RMP for the treatment of metastatic colorectal cancer.

Abstract: e14065 Background: BEVZ92 has being developed as a proposed biosimilar approved reference medicine product (RMP). BEVZ92 has an identical amino acid sequence and highly similar physicochemical and in vitro functional properties to RMP. The aim of this study was to demonstrate pharmacokinetics (PK) similarity of BEVZ92 to RMP, in combination in combination with FOLFOX or FOLFIRI, as first-line treatment in patients with mCRC (NCT02069704). Methods: PK analysis for multiple dose studies was conducted, as per gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…70 No publications on BEVZ92 were identified in the above-mentioned systematic review 16,65 ; however, the results of a comparative PK trial in patients with metastatic colorectal cancer (NCT02069704) have been published subsequently in abstract form. 71 In 2017, the manufacturer of Bevax® registered a comparative PK study (NCT03293654) and a comparative efficacy and safety study (NCT03296163) for a potential bevacizumab biosimilar identified as MB02; we presume these trials are being conducted to support regulatory submissions in other localities.…”
Section: Biosimilars In Latin America: Current Situationmentioning
confidence: 99%
“…70 No publications on BEVZ92 were identified in the above-mentioned systematic review 16,65 ; however, the results of a comparative PK trial in patients with metastatic colorectal cancer (NCT02069704) have been published subsequently in abstract form. 71 In 2017, the manufacturer of Bevax® registered a comparative PK study (NCT03293654) and a comparative efficacy and safety study (NCT03296163) for a potential bevacizumab biosimilar identified as MB02; we presume these trials are being conducted to support regulatory submissions in other localities.…”
Section: Biosimilars In Latin America: Current Situationmentioning
confidence: 99%